An embedded carbon-supported iron-based catalyst and its preparation method and application
The preparation of embedded carbon-supported iron-based catalysts by catalytic chemical vapor deposition method solves the problems of high production costs, easy reduction in activity and difficulty in recycling of precious metal catalysts, and achieves efficient hydrogenation of 4,6-dinitroresorcinol, reducing production costs and improving the stability and recyclability of the catalyst.
Patent Information
- Application Number
- CN202310584695.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-23
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-05-23
AI Technical Summary
The existing precious metal catalysts are difficult to meet the industrial production needs of 4,6-diaminoresorcinol in terms of high production costs, easy reduction in activity and difficult recycling.
An embedded carbon-supported iron-based catalyst was prepared by catalytic chemical vapor deposition method. A catalyst was formed with a surface coated with a nanocarbon layer of iron nanoparticles by using non-precious metal Fe as the main precursor, and used for the hydrogenation synthesis of 4,6-dinitroresorcinol.
It achieves efficient catalytic performance, with a conversion rate of up to 98.5%, and a selectivity of up to 95.2%, while reducing production costs and improving the stability and recyclability of the catalyst.
Smart Images

Figure CN116899567B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic materials, and in particular relates to an embedded carbon-supported iron-based catalyst and a preparation method and application thereof. Background Art
[0002] 4,6-Diaminoresorcinol (DAR) is an important monomer for synthesizing poly(p-phenylene benzobisoxazole) fiber (PBO). High-purity DAR can be used to synthesize high-performance PBO fiber. PBO fiber has a strong conjugation effect due to its rigid conjugated structure consisting of completely coplanar benzene rings and aromatic heterocycles. It has high tensile strength, good flame retardancy and high temperature resistance, and has broad application prospects in aerospace, military defense, and civilian applications. Specifically, PBO fiber can be used in the aerospace field as a base material for spacecraft and satellites, as a protective layer for space exploration vehicles, etc. due to its high temperature resistance and high strength. In the field of national defense and military, bulletproof vests can be prepared through special weaving processes, and can be used to produce reinforcement materials, bulletproof materials, armor materials, etc. for missile composite materials. In the civilian field, the good flame retardancy of PBO fiber can be used in the manufacture of protective clothing, and it also has great application prospects in the preparation of high temperature resistant materials required in the aluminum industry and glass industry.
[0003] 4,6-diaminoresorcinol can be prepared by hydrogenation reduction of 4,6-dinitroresorcinol. At present, the catalysts used for hydrogenation of nitro groups on benzene rings are mostly precious metal catalysts such as skeleton ruthenium and palladium carbon. In the preparation process of 4,6-diaminoresorcinol hydrochloride disclosed in CN107973723A, 2-chloro-4,6-dinitroresorcinol is used as raw material, Pd / C-Fe3O4 is used as catalyst, and 60% methanol aqueous solution is used as solvent to react in a high-pressure reactor. After the reaction, concentrated hydrochloric acid and stannous chloride solution are added, and the precipitate is vacuum dried at 80°C for 6h to obtain the product 4,6-diaminoresorcinol hydrochloride. However, the addition of precious metals increases the production cost of the catalyst. In addition, the catalyst is prone to agglomeration and sintering after a period of use, resulting in a significant decrease in activity. At the same time, these precious metal catalysts also have the problem of difficult recovery, which is not conducive to their industrial application.
[0004] Based on this, the development of a new catalyst that is mainly non-precious metals, has high target product yield, good stability, and is easy to recycle and reuse has high application value for the industrial production of 4,6-diaminoresorcinol (DAR). Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a novel embedded carbon-supported iron-based catalyst for hydrogenating 4,6-dinitroresorcinol to synthesize 4,6-diaminoresorcinol and a preparation method thereof. The present invention adopts a catalytic chemical vapor deposition method to prepare an embedded carbon-supported iron-based catalyst, uses non-precious metal Fe as a main precursor, and obtains an embedded carbon-supported iron-based catalyst with iron nanoparticles wrapped under a surface carbon layer through catalytic chemical vapor deposition, which is used for the efficient catalytic hydrogenation of 4,6-dinitroresorcinol to synthesize 4,6-diaminoresorcinol.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing an embedded carbon-supported iron-based catalyst comprises the following steps:
[0008] (1) mixing a dispersant, a metal precursor solution containing iron (Fe) and urea and stirring them, obtaining a solid product by a deposition precipitation method, and drying and calcining them to obtain a precursor of an embedded carbon-supported iron-based catalyst;
[0009] (2) The precursor is reduced in an inert gas / hydrogen atmosphere, and then switched to a carbon source gas of a methane / hydrogen mixed atmosphere, and carbon is deposited on the surface of the reduced precursor by chemical vapor deposition to obtain the embedded carbon-supported iron-based catalyst.
[0010] The present invention is further configured as follows: in the step (1), after dispersing the dispersant in water, a pH adjuster is added to adjust the pH of the system to acidic, and then an iron-containing metal precursor solution is added and fully stirred, and then urea is added to precipitate to obtain a solid product; after filtering and washing, the precursor is dried and calcined.
[0011] The present invention is further configured that, in the step (1),
[0012] The dispersant is selected from one of γ-Al2O3, silicon dioxide, titanium dioxide, and mica flakes;
[0013] The iron-containing metal precursor is selected from one of ferric nitrate, ferric chloride and ferric citrate, preferably ferric nitrate;
[0014] The temperature of the sedimentation is 50 to 95°C and the time is 2 to 24 hours;
[0015] The calcination temperature is 200-700°C and the calcination time is 2-12h;
[0016] The molar ratio of the urea to the iron in the iron-containing metal precursor is (5-10):1, preferably (6-7):1, and more preferably 6.7:1;
[0017] The pH adjuster is selected from nitric acid, hydrochloric acid, sulfuric acid or phosphoric acid, preferably nitric acid;
[0018] The target pH value of the adjustment system is 4-7, preferably 5-6, and more preferably 5.
[0019] The present invention is further configured such that in the step (2), after the precursor is heated to a target reduction temperature in an inert gas atmosphere, it is reduced in an inert gas / hydrogen atmosphere to obtain a reduced precursor; after the reduced precursor is heated to a target chemical vapor deposition temperature in an inert gas atmosphere, a carbon source gas in a methane / hydrogen mixed atmosphere is introduced to deposit carbon on the surface of the reduced precursor.
[0020] The present invention is further configured that, in the step (2),
[0021] The reduction temperature is 500-700°C, preferably 550-650°C, and the reduction time is 1-5h;
[0022] The chemical vapor deposition temperature is 500-900° C., preferably 550-650° C., and the chemical vapor deposition time is 0.5-12 hours.
[0023] The volume flow ratio of methane to hydrogen in the carbon source gas is (0.5-6):1, preferably (1-4):1, and more preferably (3-4):1.
[0024] The second aspect of the present invention is to provide an embedded carbon-supported iron-based catalyst prepared by the preparation method of the embedded carbon-supported iron-based catalyst. The embedded carbon-supported iron-based catalyst is a catalyst in which a nano-carbon layer is coated on the surface of iron nanoparticles. Carbon growth using methane as a carbon source induces selective exposure of Fe(110) crystal faces with high iron hydrogenation activity, thereby improving the activity and selectivity of the catalyst. In terms of mass percentage, the loading amount of active metal Fe in the embedded carbon-supported iron-based catalyst is 2 to 20 wt%, preferably 8 to 18 wt%.
[0025] The third aspect of the present invention is to provide an application of the embedded carbon-supported iron-based catalyst for the hydrogenation of 4,6-dinitroresorcinol to 4,6-diaminoresorcinol.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The present invention utilizes a catalytic chemical vapor deposition method to prepare an embedded carbon-supported iron-based catalyst with good dispersibility and uniform particle size distribution. In the deposition process of catalyzing the decomposition of methane to synthesize carbon materials, carbon growth using methane as a carbon source induces the selective exposure of Fe(110) crystal faces with high iron hydrogenation activity, thereby improving the activity and selectivity of the catalyst, and exhibiting excellent catalytic performance in the hydrogenation of 4,6-dinitroresorcinol to 4,6-diaminoresorcinol. Under relatively low reaction temperature (55°C), the conversion rate is as high as 98.5%, and the selectivity is as high as 95.2%. At the same time, in the embedded carbon-supported iron-based catalyst, the nanocarbon layer coated on the surface of the Fe nanoparticles can effectively inhibit the agglomeration of the iron nanoparticles during the hydrogenation reaction, thereby improving the anti-sintering properties of the catalyst.
[0028] (2) The embedded carbon-supported iron-based catalyst does not use traditional precious metal hydrogenation components, but uses non-precious metal Fe as the active component, which greatly reduces the production cost of the catalyst. In addition, methane is used as the carbon source gas for vapor deposition, and the source of raw materials is wide. At the same time, the catalyst has strong magnetism due to its high iron content. At the end of the reaction, the catalyst can be recovered by a magnet, which improves the recycling rate of the catalyst. The embedded carbon-supported iron-based catalyst greatly reduces the production cost of synthesizing 4,6-diaminoresorcinol by hydrogenation of 4,6-dinitroresorcinol, has good stability, can be recycled, and its catalytic performance can reach the level of traditional supported precious metal hydrogenation catalysts, and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The transmission electron microscope images and tube diameter distribution diagrams of the prepared catalysts S4 and S2;
[0030] Figure 2 is the XRD pattern of the prepared catalyst S4;
[0031] Figure 3 The catalytic performance change diagram of the prepared catalyst S4 after five cycle experiments. DETAILED DESCRIPTION
[0032] After extensive and in-depth research, the inventors have provided a method for preparing an embedded carbon-supported iron-based catalyst with highly dispersed iron nanoparticles. The method includes two steps: one is the synthesis of an iron-containing precursor; the other is the preparation of the catalyst by catalyzing the gas phase chemical deposition of methane using the iron-containing precursor.
[0033] 1. Synthesis of Iron-Containing Precursors
[0034] The present invention adopts a deposition precipitation method to synthesize an iron-containing precursor. A dispersant, an iron-containing metal precursor solution and urea are mixed in a certain proportion, and the pH of the mixed solution is adjusted to precipitate the solid product at a certain temperature, and the iron-containing precursor of the catalyst is obtained by filtering, washing, drying and calcining. Among them, the decomposition rate of urea in the mixed solution can be adjusted by controlling the temperature of the deposition, so that the solution is weakly alkaline and the distribution of iron ions on the surface of the dispersant is further adjusted, and finally an iron-containing precursor with uniform particle size and high dispersion is obtained.
[0035] In a preferred embodiment of the present invention, the above method specifically comprises the following steps:
[0036] The first step is to disperse the dispersant γ-Al2O3 in water and add nitric acid to adjust the pH to 5;
[0037] In the second step, the solution containing γ-Al2O3 is heated to 85°C in a constant temperature oil bath, and the ferric nitrate solution is added and stirred for 15 minutes to allow it to be adsorbed on the carrier, and urea is added and the solid product is obtained by precipitation under the condition of maintaining the oil bath temperature at 85°C for 15 hours;
[0038] The third step is to filter the mixture, wash it with a large amount of ultrapure water until it becomes neutral, dry it, and calcine it at 600° C. to obtain the iron-containing precursor.
[0039] The iron oxide grain size distribution on the precursor obtained by the method is 20-35nm, the iron oxide particles are uniform in size and evenly distributed, and can fully catalyze methane gas phase chemical deposition.
[0040] 2. Preparation of embedded carbon-supported iron-based catalyst by catalytic chemical vapor deposition
[0041] The iron-containing precursor synthesized above is used to prepare an embedded carbon-supported iron-based catalyst by catalyzing methane gas phase chemical deposition. The iron nanoparticles in the prepared catalyst are highly dispersed, and their surfaces are wrapped by a carbon layer. In addition, the carbon deposition induces the exposure of the Fe (110) crystal plane with high hydrogenation activity.
[0042] In a preferred embodiment of the present invention, the above method specifically comprises the following steps:
[0043] The first step is to heat the precursor to a reduction temperature of 500-700° C. under the protection of an inert gas, and reduce it for 3 hours under the conditions of hydrogen and an inert gas to obtain a reduced precursor in which the active component iron nanoparticles are highly dispersed;
[0044] In the second step, the reduced precursor is heated to a gas phase chemical vapor deposition temperature of 500-900°C under the protection of an inert gas, and the active component is used to introduce a carbon source gas of methane and hydrogen in a high temperature tube furnace, and the volume flow ratio of methane to hydrogen is (1-4):1, and carbon is deposited on the surface of the iron nanoparticles by catalytic gas phase chemical deposition for 3 hours. The carbon growth process induces the selective exposure of the Fe (110) crystal face with high iron hydrogenation activity, and finally the embedded carbon-supported iron-based catalyst is obtained. The catalyst shows a high catalytic performance for hydrogenating 4,6-dinitroresorcinol to 4,6-diaminoresorcinol.
[0045] The catalyst obtained by the above method is used for the hydrogenation reaction of 4,6-dinitroresorcinol to synthesize 4,6-diaminoresorcinol. The catalyst and methanol reactant solution are added to a reactor, the temperature is raised to the reaction temperature under the protection of inert gas, hydrogen is introduced, and a certain pressure is maintained to carry out the hydrogenation reaction.
[0046] In a preferred embodiment of the present invention, the above method specifically comprises the following steps:
[0047] In the first step, 10 mg of the catalyst was added to a 100 mL reactor liner, the raw material 4,6-dinitroresorcinol was dissolved in methanol at a concentration of 1 g / L, and 60 mL of the methanol reactant solution was added to the reactor liner;
[0048] In the second step, the temperature was raised to a reaction temperature of 55°C under the protection of 1.0 MPa argon, hydrogen was introduced into the reactor, and the pressure was maintained at 1.0 MPa to carry out a hydrogenation reaction.
[0049] The reaction products were sampled every 20 min and quantitatively analyzed by liquid chromatography.
[0050] The technical scheme of the present invention is described clearly and completely with specific embodiments below. It should be understood that the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of the present invention. The experimental methods without specifying specific conditions in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer. Unless otherwise defined, all professional and scientific terms used in the text have the same meanings as those familiar to those skilled in the art. The units in the weight volume percentage in the present invention are well known to those skilled in the art, for example, refer to the weight of the solute in 100 ml of solution.
[0051] Example 1
[0052] (1) Add 3 g of commercial γ-Al2O3 as a dispersant to ultrapure water at room temperature, stir at room temperature to form a suspension, and then add nitric acid dropwise until the solution pH = 5; transfer the above solution to a 500 mL three-necked flask and heat to 85°C, weigh 2 g of Fe(NO3)3·9H2O and add it to the three-necked flask, and stir for 15 min; weigh 2 g of urea and dissolve it in 100 mL of ultrapure water, add it to the three-necked flask, stir at 85°C for 15 h to obtain a solid-liquid mixture, and cool to room temperature; filter the solid-liquid mixture at room temperature to obtain a solid precipitate, and wash the precipitate with ultrapure water 3 times. The obtained precipitate is dried overnight, ground, and calcined in a muffle furnace at 600°C for 4 h to obtain a precursor;
[0053] (2) Take 0.5 g of the precursor and spread it evenly in a quartz boat, and place the quartz boat in a high-temperature tube furnace; raise the temperature to 600°C under argon protection, adjust the hydrogen flow rate to 75 mL / min, and the argon flow rate to 25 mL / min, to obtain a reduced precursor; maintain the catalytic deposition temperature at 600°C, the methane flow rate to 80 mL / min, and the hydrogen flow rate to 20 mL / min for 3 hours; turn off the hydrogen and methane, and drop the temperature to room temperature under argon protection to obtain the embedded carbon-supported iron-based catalyst S1.
[0054] Transmission electron microscopy analysis of the obtained embedded carbon-supported iron-based catalyst showed that the iron particles in the catalyst had uniform particle size and were evenly distributed; the tube diameter of the nanocarbon material was 10.3 nm; the size of the iron particles was close to the diameter of the nanocarbon material, slightly smaller than the tube diameter; XRD test showed that the iron phase in the catalyst was elemental iron.
[0055] The obtained catalyst was used for the hydrogenation of 4,6-dinitroresorcinol to 4,6-diaminoresorcinol, with a 4,6-dinitroresorcinol conversion rate of 98.5% and a 4,6-diaminoresorcinol selectivity of 92.1%. The specific catalyst characteristics and reaction activity are shown in Table 1 below.
[0056] Example 2
[0057] According to the method of Example 1, the concentration of ferric nitrate in the mixed solution was changed to prepare an embedded carbon-supported iron-based catalyst.
[0058] (1) Add 3 g of commercial γ-Al2O3 as a dispersant to ultrapure water at room temperature, stir at room temperature to form a suspension, and then add nitric acid dropwise until the solution pH = 5; transfer the above solution to a 500 mL three-necked flask and heat to 85°C, weigh 4 g, 12 g, 16 g or 24 g of Fe(NO3)3·9H2O and add it to the three-necked flask, and stir for 15 min; weigh 4 g, 12 g, 16 g or 24 g of urea and dissolve it in 100 mL of ultrapure water, add it to the three-necked flask, stir at 85°C for 15 h to obtain a solid-liquid mixture, and cool to room temperature; filter the solid-liquid mixture at room temperature to obtain a solid precipitate, and wash the precipitate with ultrapure water for 3 times. The obtained precipitate is dried overnight, ground, and calcined in a muffle furnace at 600°C for 4 h to obtain a precursor;
[0059] (2) Take 0.5 g of the precursor and spread it evenly in a quartz boat, and place the quartz boat in a high-temperature tube furnace; raise the temperature to 600°C under argon protection, adjust the hydrogen flow rate to 75 mL / min, and the argon flow rate to 25 mL / min, to obtain a reduced precursor; maintain the carbon deposition temperature at 600°C, the methane flow rate to 80 mL / min, and the hydrogen flow rate to 20 mL / min for 3 hours; turn off the hydrogen and methane, and cool to room temperature under argon protection to obtain embedded carbon-supported iron-based catalysts S2S3, S4, and S5.
[0060] The obtained embedded carbon-supported iron-based catalyst was analyzed by transmission electron microscopy. The transmission electron microscopy images of catalysts S2 and S4 and the tube diameter distribution of nanocarbon materials are shown in Figure 1 As shown, (1) and (2) are transmission electron microscope images and tube diameter distribution diagrams of catalyst S4; (3) and (4) are transmission electron microscope images and tube diameter distribution diagrams of catalyst S2. The iron particles have uniform particle size and are evenly distributed. The size of the iron particles is close to the diameter of the nanocarbon material and is slightly smaller than the tube diameter.
[0061] The XRD pattern of catalyst S4 is shown in Figure 2 As shown, the physical phase of iron in the catalyst is elemental iron.
[0062] The catalytic performance of catalyst S4 after 5 cycles of hydrogenation of 4,6-dinitroresorcinol to 4,6-diaminoresorcinol was shown in the following figure: Figure 3 As shown, after 5 cycles of experiments, the product yield did not decrease significantly. The specific catalyst characteristics and reaction activities are shown in Table 1 below.
[0063] Example 3
[0064] According to the method of Example 1, the deposition temperature in the high-temperature tube furnace was changed to prepare an embedded carbon-supported iron-based catalyst.
[0065] (1) Add 3 g of commercial γ-Al2O3 as a dispersant to ultrapure water at room temperature, stir at room temperature to form a suspension, and then add nitric acid dropwise until the solution pH = 5; transfer the above solution to a 500 mL three-necked flask and heat to 85°C, weigh 16 g of Fe(NO3)3·9H2O and add it to the three-necked flask, and stir for 15 min; weigh 16 g of urea and dissolve it in 100 mL of ultrapure water, add it to the three-necked flask, stir at 85°C for 15 h to obtain a solid-liquid mixture, and cool to room temperature; filter the solid-liquid mixture at room temperature to obtain a solid precipitate, and wash the precipitate with ultrapure water 3 times. The obtained precipitate is dried overnight, ground, and calcined in a muffle furnace at 600°C for 4 h to obtain a precursor;
[0066] (2) Take 0.5 g of the precursor and spread it evenly in a quartz boat, and place the quartz boat in a high-temperature tube furnace; heat it to 600°C under argon protection, adjust the hydrogen flow rate to 75 mL / min and the argon flow rate to 25 mL / min, and obtain the reduced precursor; heat it to the carbon deposition temperature of 700, 800 or 900°C, and maintain it for 3 hours under the conditions of methane flow rate of 80 mL / min and hydrogen flow rate of 20 mL / min; turn off the hydrogen and methane, and cool it to room temperature under argon protection to obtain embedded carbon-supported iron-based catalysts S6, S7, and S8.
[0067] The obtained embedded carbon-supported iron-based catalyst was analyzed by transmission electron microscopy and used in the hydrogenation of 4,6-dinitroresorcinol to synthesize 4,6-diaminoresorcinol. The specific catalyst characteristics and reaction activity are shown in Table 1 below.
[0068] Example 4
[0069] According to the method of Example 1, the volume flow ratio of methane to hydrogen in the high-temperature tube furnace was changed to prepare an embedded carbon-supported iron-based catalyst.
[0070] (1) Add 3 g of commercial γ-Al2O3 as a dispersant to ultrapure water at room temperature, stir at room temperature to form a suspension, and then add nitric acid dropwise until the solution pH = 5; transfer the above solution to a 500 mL three-necked flask and heat to 85°C, weigh 16 g of Fe(NO3)3·9H2O and add it to the three-necked flask, and stir for 15 min; weigh 16 g of urea and dissolve it in 100 mL of ultrapure water, add it to the three-necked flask, stir at 85°C for 15 h to obtain a solid-liquid mixture, and cool to room temperature; filter the solid-liquid mixture at room temperature to obtain a solid precipitate, and wash the precipitate with ultrapure water 3 times. The obtained precipitate is dried overnight, ground, and calcined in a muffle furnace at 600°C for 4 h to obtain a precursor;
[0071] (2) Take 0.5 g of the precursor and spread it evenly in a quartz boat, and place the quartz boat in a high-temperature tube furnace; raise the temperature to 600°C under argon protection, adjust the hydrogen flow rate to 75 mL / min and the argon flow rate to 25 mL / min, and obtain the reduced precursor; maintain the carbon deposition temperature at 600°C, maintain the total methane and hydrogen flow rate at 100 mL / min, change the volume flow ratio of methane and hydrogen to 3:1, 2:1, 1:1, and maintain for 3 hours; turn off hydrogen and methane, and cool to room temperature under argon protection to obtain embedded carbon-supported iron-based catalysts S9, S10, and S11.
[0072] The obtained embedded carbon-supported iron-based catalyst was analyzed by transmission electron microscopy and used in the hydrogenation of 4,6-dinitroresorcinol to synthesize 4,6-diaminoresorcinol. The specific catalyst characteristics and reaction activity are shown in Table 1 below.
[0073] Comparative Example 1
[0074] According to the method of Example 1, an embedded carbon-supported iron-based catalyst is prepared, the main difference being that the carbon source gas in step (2) is a mixed gas of carbon monoxide and hydrogen.
[0075] (1) Add 3 g of commercial γ-Al2O3 as a dispersant to ultrapure water at room temperature, stir at room temperature to form a suspension, and then add nitric acid dropwise until the solution pH = 5; transfer the above solution to a 500 mL three-necked flask and heat to 85°C, weigh 16 g of Fe(NO3)3·9H2O and add it to the three-necked flask, and stir for 15 min; weigh 16 g of urea and dissolve it in 100 mL of ultrapure water, add it to the three-necked flask, stir at 85°C for 15 h to obtain a solid-liquid mixture, and cool to room temperature; filter the solid-liquid mixture at room temperature to obtain a solid precipitate, and wash the precipitate with ultrapure water 3 times. The obtained precipitate is dried overnight, ground, and calcined in a muffle furnace at 600°C for 4 h to obtain a precursor;
[0076] (2) Take 0.5 g of the precursor and spread it evenly in a quartz boat, and place the quartz boat in a high-temperature tube furnace; raise the temperature to 600°C under argon protection, adjust the hydrogen flow rate to 75 mL / min and the argon flow rate to 25 mL / min, and obtain the reduced precursor; maintain the catalytic deposition temperature at 600°C, maintain the total flow rate of carbon monoxide and hydrogen at 100 mL / min, and change the volume flow ratio of carbon monoxide and hydrogen to 4:1, 3:1, and 2:1 for 3 hours; turn off hydrogen and carbon monoxide, and cool the temperature to room temperature under argon protection to obtain embedded carbon-supported iron-based catalysts S12, S13, and S14.
[0077] The obtained catalyst was analyzed by transmission electron microscopy and used in the hydrogenation of 4,6-dinitroresorcinol to 4,6-diaminoresorcinol. The specific catalyst characteristics and reaction activity are shown in Table 1 below.
[0078] As shown in Table 1, the characteristics of different catalyst parameters and the results of catalytic hydrogenation of 4,6-dinitroresorcinol to 4,6-diaminoresorcinol are shown. The reaction results include the conversion rate of the reactant 4,6-dinitroresorcinol, the selectivity of the product 4,6-diaminoresorcinol, and the yield of the product 4,6-diaminoresorcinol. During the reaction, the hydrogen pressure in the reactor was maintained at 1.0 MPa and the temperature was maintained at 55°C.
[0079] Table 1
[0080]
[0081]
[0082] In terms of mass percentage, the loading amount of active metal Fe in the embedded carbon-supported iron-based catalyst is 8-18wt%, the diameter of the carbon fiber coated with the iron nanoparticles is in the range of 10-35nm, and under the condition of relatively low reaction temperature (55°C), the catalyst can catalyze the hydrogenation of 4,6-dinitroresorcinol to synthesize 4,6-diaminoresorcinol, with a conversion rate greater than 95%, as high as 98.5%, and a selectivity greater than 91%, as high as 95.2%.
[0083] When the carbon source atmosphere is replaced by CO and H2, the amount of deposited carbon layer is significantly reduced, the loading amount of active metal Fe is significantly increased, and at the same time, the diameter of the carbon fiber tube coated with iron nanoparticles is significantly increased, resulting in a decrease in catalytic performance in the reaction of hydrogenation of 4,6-dinitroresorcinol to 4,6-diaminoresorcinol.
[0084] This application is described in detail for the purpose of enabling those skilled in the art to understand the contents of this application and implement them. This is not intended to limit the scope of protection of this application. Any equivalent changes or modifications made according to the spirit of this application should be included in the scope of protection of this application.
Claims
1. An application of an embedded carbon-supported iron-based catalyst in the hydrogenation of 4,6-dinitroresorcinol to 4,6-diaminoresorcinol, characterized in that: The preparation method of the embedded carbon-supported iron-based catalyst comprises the following steps: (1) After dispersing the dispersant in water, a pH adjuster is added to adjust the pH of the system to acidic, and then an iron-containing metal precursor solution is added and stirred sufficiently, and then urea is added to precipitate to obtain a solid product; after filtering and washing, the precursor is dried and calcined; the dispersant is selected from one of γ-Al2O3, silicon dioxide, titanium dioxide, and mica flakes; the temperature of the precipitation is 50-95°C, and the time is 2-24 h; the temperature of the calcination is 200-700°C, and the time is 2-12 h; (2) After the precursor is heated to a target reduction temperature in an inert gas atmosphere, it is reduced in an inert gas / hydrogen atmosphere to obtain a reduced precursor; after the reduced precursor is heated to a target chemical vapor deposition temperature in an inert gas atmosphere, a carbon source gas in a methane / hydrogen mixed atmosphere is introduced to deposit carbon on the surface of the reduced precursor to obtain the embedded carbon-supported iron-based catalyst.
2. The use according to claim 1, characterized in that: In the step (1), the iron-containing metal precursor is selected from one of ferric nitrate, ferric chloride and ferric citrate.
3. The use according to claim 1, characterized in that: In the step (1), the molar ratio of the urea to the iron in the iron-containing metal precursor is (5-10):1; the pH adjuster is selected from nitric acid, hydrochloric acid, sulfuric acid or phosphoric acid, and the target pH value of the adjustment system is 4-7.
4. The use according to claim 1, characterized in that: The molar ratio of urea to iron in the iron-containing metal precursor in step (1) is (6-7):
1.
5. The use according to claim 1, characterized in that: In the step (2), the reduction temperature is 500-700° C., and the reduction time is 1-5 h.
6. The use according to claim 1, characterized in that: In the step (2), the chemical vapor deposition temperature is 500-900°C, and the chemical vapor deposition time is 0.5-12 h.
7. The use according to claim 1, characterized in that: In the step (2), the volume flow ratio of methane to hydrogen in the carbon source gas is (0.5-6):
1.
8. The use according to claim 1, characterized in that: In the step (2), the volume flow ratio of methane to hydrogen in the carbon source gas is (1-4):
1.
9. The use according to any one of claims 1 to 8, characterized in that: The embedded carbon-supported iron-based catalyst is a catalyst in which the surface of iron nanoparticles is coated with a nanocarbon layer. In terms of mass percentage, the loading amount of active metal Fe in the embedded carbon-supported iron-based catalyst is 2-20 wt%.
10. The use according to any one of claims 1 to 8, characterized in that: The embedded carbon-supported iron-based catalyst is a catalyst in which the surface of iron nanoparticles is coated with a nanocarbon layer. In terms of mass percentage, the loading amount of active metal Fe in the embedded carbon-supported iron-based catalyst is 8-18 wt%.
Citation Information
Patent Citations
4,6-diaminoresorcinol hydrochloride preparation method
CN107973723A
Production of 4,6-diaminoresorcin and its salt
JP1995233127A